Labor Market Institutions and Long-Term Effects of Youth Unemployment - Daiji Kawaguchi; Tetsushi Murao (Institute for the Study of Labor (IZA), 2014)
Graduating from a school during a time of adverse economic conditions has a persistent, harmful effect on workers' subsequent employment opportunities. An analysis of panel data from OECD countries during the 1960-2010 periods reveals that a worker who experiences a one-percentage-point higher unemployment rate while the worker is 16-24 years old has a 0.14 percentage-point higher unemployment rate at ages 25-29 and 0.03 percentage points higher at ages 30-34. The persistence of this negative effect is stronger in countries with stricter employment protection legislation. A composite index for labor market rigidity is constructed and the index is shown to have positive correlation with the persistence. Moderating macroeconomic fluctuations is more important in countries that have more persistent labor-market entry effects on subsequent outcomes.
Keywords: E24; J64; J65; K31; 330; cohort analysis; port of entry; hysteresis; persistence; unemployment